Multi-sensor Satellite Drought Analysis using Landsat and MODIS Time-Series Based on NDVI and Rainfall - Sara Hayman Zaki; Heman Abdulkhaleq A. Gaznayee; Payam Salah Hawez (Zanco Journal of Pure and Applied Sciences, 2023)
Iraq's climate is prone to frequent droughts, which have severely influenced the country in the past two decades. A study conducted using remote sensing and geographical information systems analyzed the spatiotemporal patterns of drought in Iraqi Kurdistan - specifically Erbil for 19 years from 2003 to 2021. The research found that the region had experienced severe drought episodes during this time, with an increase in severity and frequency, especially in 2008, 2012, and 2021. These years were noticeable by a decrease in vegetation area cover and lower average precipitation. The study utilized the Normalized Difference Vegetation Index (NDVI), Rainfall, and Rainfall Anomaly to produce multi-temporal classified drought maps, which showed that climate conditions played a significant role in the change of the vegetated cover area. The research also estimated the effect of rainfall variability on vegetation cover in Erbil, concluding that rainfall anomalies led to changes in the NDVI. The correlation matrix between rainfall anomalies and NDVI anomalies confirms that irregular rainfall patterns result in modifications to the NDVI. Productivity was found to increase with wet anomalies and decrease with dry anomalies. Overall, the study provides valuable insights into the impact of drought on agricultural productivity in the Iraqi Kurdistan Region (IKR)-Erbil and emphasizes the importance of implementing effective strategies to mitigate the impact of drought on agriculture in the region.